IMPLEMENTASI METODE ONE DAY ONE AYAT DALAM MENINGKATKAN KEMAMPUAN MENGHAFAL JUZ 30 DI PONDOK PESANTREN SAADATUL MUTTAQIN MUARO JAMBI - Azizah, Ronia; Anwar, Kasful; Madyan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The ability to memorize the Qur’an, especially Juz 30, requires an effective and appropriate method to help students improve the quality and consistency of their memorization. However, various obstacles such as limited memorization skills, lack of fluency, difficulties in applying tajwid rules, and differences in students’ memorization abilities remain challenges in the learning process. This study aims to analyze the implementation of the One Day One Ayat (ODOA) method in improving the ability to memorize Juz 30 among students at Saadatul Muttaqin Islamic Boarding School, Muaro Jambi. This study employed a qualitative approach with a case study design. The participants consisted of Islamic teachers and students involved in the implementation of the ODOA method. Data were collected through observations, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing. The findings revealed that the implementation of the ODOA method was conducted through three stages, namely planning, implementation, and evaluation. The method was effective in improving students’ memorization abilities because it allowed them to memorize the Qur’an gradually, increased their motivation, improved memorization accuracy, and facilitated regular revision (muroja’ah). The success of the method was supported by teachers’ guidance, students’ commitment, and a conducive learning environment, while differences in students’ abilities and consistency in memorization became the main challenges. Therefore, the ODOA method can be considered as an effective strategy in enhancing the quality of Qur’anic memorization among students.